Experimental Autoimmune Encephalomyelitis in the Mouse. Issue 12 (6th December 2021) - Laaker, Collin; Hsu, Martin; Fabry, Zsuzsanna; Miller, Stephen D.; Karpus, William J.
Abstract: This article details the materials and methods required for both active induction and adoptive transfer of experimental autoimmune encephalomyelitis (EAE) in the SJL mouse strain using intact proteins or peptides from the two major myelin proteins: proteolipid protein (PLP) and myelin basic protein (MBP). Additionally, active induction of EAE in the C57BL/6 strain using myelin oligodendrocyte glycoprotein (MOG) peptide is also discussed. Detailed materials and methods required for the purification of both PLP and MBP are described, and a protocol for isolating CNS‐infiltrating lymphocytes in EAE mice is included. Modifications of the specified protocols may be necessary for efficient induction of active or adoptive EAE in other mouse strains. © 2021 Wiley Periodicals LLC. Basic Protocol : Active induction of EAE with PLP, MBP, and MOG protein or peptide Alternate Protocol : Adoptive induction of EAE with PLP‐, MBP‐, or MOG‐specific lymphocytes Support Protocol 1 : Purification of proteolipid protein Support Protocol 2 : Purification of myelin basic protein Support Protocol 3 : Isolation of CNS‐infiltrating lymphocytes